From Maxwell's equations to the theory of current‐source density analysis. (28th March 2017) - Gratiy, Sergey L.; Halnes, Geir; Denman, Daniel; Hawrylycz, Michael J.; Koch, Christof; Einevoll, Gaute T.; Anastassiou, Costas A.
Abstract: Despite the widespread use of current‐source density (CSD) analysis of extracellular potential recordings in the brain, the physical mechanisms responsible for the generation of the signal are still debated. While the extracellular potential is thought to be exclusively generated by the transmembrane currents, recent studies suggest that extracellular diffusive, advective and displacement currents—traditionally neglected—may also contribute considerably toward extracellular potential recordings. Here, we first justify the application of the electro‐quasistatic approximation of Maxwell's equations to describe the electromagnetic field of physiological origin. Subsequently, we perform spatial averaging of currents in neural tissue to arrive at the notion of the CSD and derive an equation relating it to the extracellular potential. We show that, in general, the extracellular potential is determined by the CSD of membrane currents as well as the gradients of the putative extracellular diffusion current. The diffusion current can contribute significantly to the extracellular potential at frequencies less than a few Hertz; in which case it must be subtracted to obtain correct CSD estimates. We also show that the advective and displacement currents in the extracellular space are negligible for physiological frequencies while, within cellular membrane, displacement current contributes toward the CSD as a capacitive current. Taken together, these findings elucidate the relationship between electric currents and the extracellular potential in brain tissue and form the necessary foundation for the analysis of extracellular recordings. Abstract : We revisit the assumptions and rigorously derive the theory of current‐source density analysis. It is shown that the extracellular potential is generally determined by the transmembrane currents as well as the putative extracellular diffusion currents, which can play an important role at the lowest frequencies. In turn, the effect of the extracellular advective and displacement currents on the extracellular potential is negligible for physiological frequencies.